Dual butler matrix active antenna system - Abdul Rahim, Sharul Kamal; Gardner, Peter (John Wiley & Sons, Ltd, 2007)
This article describes a smart antenna system that employs low noise amplifiers and two cascaded Butler Matrices. The output signals from the first Butler Matrix, which acts as a beamforming network, have high gain and narrowbeam width for long distance communication while the outputs from the second Butler Matrix, which acts as a mirror of the first Butler Matrix, reconstructing the antenna patterns of the individual radiating elements, have high linearity and broad beam width that can be used for short distance communication. Switching or selecting between the two sets of beams allows reception to be optimized for either vehicle to vehicle or vehicle to roadside beacon communications.